Konsep Gerak Mullȃ Sadrȃ: Suatu Tinjauan Filsafat - Arsyad Arsyad (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
Mullȃ Sadrȃ proves that all nature and all objects that assimilate space and time are always in constant fluctuations. The Motion on objects is not limited to accidents and external conditions, but the substance. If the substance of these objects did not change, their conditions, characteristics, and accidents would not change. More than that, Mullȃ Sadr states that all substances and things keep changing so that all things are not related to change, existence and transition itself. According to Mullȃ Sadrȃ, motion is a change in an object of potentiality towards actuality. An important point in the discussion about motion is that potentiality and actuality are things that are simultaneously from existence to existence. Here, one can conclude the reality and existence of motion and also consider it a philosophical problem. Therefore, it will be the responsibility of the philosophers to examine it.